PENGARUH MEDIA CANVA DALAM MENULIS TEKS IKLAN SISWA KELAS VIII SMP SRIGUNA PALEMBANG - Rahayu, Putri; Dian Nuzulia Armiriena; Nufus, Hayatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students who have difficulty in writing advertising texts, especially in terms of linguistic rules and using creative ideas. The purpose of this study is to determine and describe the influence of advertising text media on the writing of advertising texts by eighth-grade students of SMP Sriguna Palembang. This research method is an experimental quantitative approach. The results of the research show that from the test results conducted in writing advertising texts, the average score obtained in the experimental class is 77.72 and in the control class is 48.60. Based on hypothesis testing using the t-test, it is known that the calculated t value is 2.803 with degrees of freedom (N1+N2)-2: (25+25)-2: 48, thus the table t value is 2.232, therefore Ho hypothesis is rejected and Ha is accepted, it can be concluded that there is an influence of Canva media on the writing skills of advertising texts in eighth-grade students of SMP Sriguna Palembang.